2004
DOI: 10.1111/j.1748-7692.2004.tb01151.x
|View full text |Cite
|
Sign up to set email alerts
|

GEOGRAPHIC GENETIC STRUCTURE IN THE FRANCISCANA DOLPHIN (PONTOPORIA BLAINVILLEI)

Abstract: The franciscana, Pontoporia blainvillei, is endemic to the South Atlantic coast of South America. The species is of conservation concern because it suffers elevated mortality rates due to incidental captures in fishing nets, and perhaps it is one of the most threatened small cetaceans in this region. Previous morphological and genetic studies have suggested the existence of at least two distinct stocks to the north and south of Santa Catarina Island in Brazil. Fixed differences were found between a sample from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(87 citation statements)
references
References 35 publications
9
73
0
Order By: Relevance
“…This suggested a model based upon a single sample of both sexes, with its increased precision due to larger sample size, may be preferable. Several morphometric and genetic studies (Pinedo, 1991(Pinedo, , 1995Secchi et al, 1998Secchi et al, , 2003aOtt et al, 2002;Ramos et al, 2002;Lázaro et al, 2004;Barreto and Rosas, 2006) have established the existence of three franciscana morphotypes/genotypes: one found in FMA I (Rio de Janeiro and Espírito Santo states, Brazil); a second one in FMA II (from São Paulo to Santa Catarina states, Brazil) and the third in FMA III and IV (from Rio Grande do Sul state, Brazil down to Buenos Aires Province, Argentina). Animals inhabiting FMA I are smaller than animals from FMA III and IV but larger than those from FMA II.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested a model based upon a single sample of both sexes, with its increased precision due to larger sample size, may be preferable. Several morphometric and genetic studies (Pinedo, 1991(Pinedo, , 1995Secchi et al, 1998Secchi et al, , 2003aOtt et al, 2002;Ramos et al, 2002;Lázaro et al, 2004;Barreto and Rosas, 2006) have established the existence of three franciscana morphotypes/genotypes: one found in FMA I (Rio de Janeiro and Espírito Santo states, Brazil); a second one in FMA II (from São Paulo to Santa Catarina states, Brazil) and the third in FMA III and IV (from Rio Grande do Sul state, Brazil down to Buenos Aires Province, Argentina). Animals inhabiting FMA I are smaller than animals from FMA III and IV but larger than those from FMA II.…”
Section: Discussionmentioning
confidence: 99%
“…Secchi and colleagues (Secchi et al 1998) performed a genetic analysis based on control region mtDNA data from 10 individuals from Rio de Janeiro and 10 individuals from Rio Grande do Sul, and suggested that these were two genetically distinct populations, supporting Pinedo (1991). Subsequently, Lazaro and colleagues (Lazaro et al 2004) used control region mtDNA data from 94 individuals sampled in Uruguay, in Buenos Aires, and from those previously studied by Secchi et al (1998) in Brazil. This recent study agreed with Secchi et al (1998) findings and further suggested the presence of two additional populations, one in what they called Rio de la Plata (Uruguay and northern Buenos Aires combined) and the other in Claromeco, Argentina.…”
Section: Introductionmentioning
confidence: 99%
“…Franciscana shows a continuous presence along the coastal area of Buenos Aires Province (Corcuera, 1994). Recent studies conducted by Lázaro et al (2004) and Ott et al (2005) 8 described a substantial geographic heterogeneity in its distribution, particularly in the southern Buenos Aires Province, suggesting this area should be considered separately. Moreover, Mendez et al (2007) suggest that the franciscana population in The International Whaling Commission Scientific Committee (Donovan and Bjørge, 1995) has noted that incidental mortality estimates of 1% per year of an estimated population size are sufficient to concern over the status of small cetacean population and the catches of 2% per year may not be sustainable.…”
Section: Discussionmentioning
confidence: 99%